2015
DOI: 10.1111/risa.12386
|View full text |Cite
|
Sign up to set email alerts
|

Transparency in Europe: A Quantitative Study

Abstract: In recent years, European pharmaceutical regulators have increasingly committed to heightening access to raw safety-related data as part of a wave of transparency initiatives (e.g., providing public Internet-mediated access to clinical trials data). Yet, the regulators--who are under significant pressure--have not yet benefited from a systematic review of this new policy. In seeking to inject much needed evidence, this article explores the effects of new transparency policies designed to promote meaningful com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 57 publications
4
84
1
Order By: Relevance
“…Similarly, while we have found that although public and patients would welcome raw and uncertain scientific data entering the public domain, they would, however, become concerned, worried and/or confused about what the complicated data actually means with many saying that they would stop taking their medicines were it published online on a public website (Bouder et al 2015;Lofstedt and Bouder 2013;Lofstedt and Way 2014a and b). Finally, there is a need to remember that data dumping is not science communication.…”
Section: 2mentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, while we have found that although public and patients would welcome raw and uncertain scientific data entering the public domain, they would, however, become concerned, worried and/or confused about what the complicated data actually means with many saying that they would stop taking their medicines were it published online on a public website (Bouder et al 2015;Lofstedt and Bouder 2013;Lofstedt and Way 2014a and b). Finally, there is a need to remember that data dumping is not science communication.…”
Section: 2mentioning
confidence: 96%
“…Move away from fish bowl transparency to science based transparency There is a need for science based regulators such as EFSA or EMA to move away from fish bowl transparency and move to science based transparency, where some specific data is shared but at the same time explained (Bouder et al 2015). The push for dumping data on line, putting clinical trials into the public domain, recording scientific debates as well as arguing for ever stricter conflict of interest statements do not lead to more trusted regulatory agencies or better policy making (Bouder et al 2015;Way and Lofstedt 2015).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…By bringing new information to the table including critique of regulatory follow-up, the regulatory body appeared left with no other option than to re-open the case. They then continued with a strategy of transparency (Bouder et al 2015), uncommon in a Norwegian setting, releasing draft report to the public, inviting experts to provide input, reflecting upon the media role and by making new safety recommendations to a wide range of actors.…”
Section: Media As Whistleblower In Risk Communicationmentioning
confidence: 99%
“…More information and more communication do not necessarily lead to better decisions about risk, and the call for increased transparency may also increase costs and complicate decision-making processes (Han 2015;Hood and Dixon 2015). Some transparency strategies may involve dedicated web portals, publication of recommendations, introduction of public hearings, establishment of safety and quality committees and disclosure of the minutes of meetings and meeting agendas (Bouder et al 2015).…”
Section: Introductionmentioning
confidence: 99%